Multilevel factors associated with inequities in multidisciplinary cancer consultation. (15th June 2022) - Sanchez, Janeth I.; Doose, Michelle; Zeruto, Chris; Chollette, Veronica; Gasca, Natalie; Verhoeven, Dana; Weaver, Sallie J.
Abstract: Objective: To assess changes in the prevalence of multidisciplinary cancer consultations (MDCc) over the last decade and examine patient, surgeon, hospital, and neighborhood factors associated with receipt of MDCc among individuals diagnosed with cancer. Data Source: Surveillance, Epidemiology and End Results (SEER)–Medicare data from 2006 to 2016. Study Design: We used time‐series analysis to assess change in MDCc prevalence from 2007 to 2015. We also conducted multilevel logistic regression with random surgeon‐ and hospital‐level effects to assess associations between patient, surgeon, neighborhood, and health care organization‐level factors and receipt of MDCc during the cancer treatment planning phase, defined as the 2 months following cancer diagnosis. Data Collection/Extraction Methods: We identified Medicare beneficiaries >65 years of age with surgically resected breast, colorectal (CRC), or non‐small cell lung cancer (NSCLC) stages I–III ( n = 103, 250). Principal Findings: From 2007 to 2015, the prevalence of MDCc increased from 35.0% to 61.2%. Overall, MDCc was most common among patients with breast cancer compared to CRC and NSCLC. Cancer patients who were Black, had comorbidities, had dual Medicare‐Medicaid coverage, were residing in rural areas or in areas with higher Black and Hispanic neighborhood composition were significantly less likely to have received MDCc. Patients receiving surgery at disproportionate payment‐sharing or rural‐designated hospitals had 2% (95% CI: −3.55, 0.58) and 17.6% (95% CI: −21.45, 13.70), respectively, less probability of receiving MDCc. Surgeon‐ and hospital‐level effects accounted for 15% of the variance in receipt of MDCc. Conclusions: The practice of MDCc has increased over the last decade, but significant geographical and health care organizational barriers continue to impede equitable access to and delivery of quality care across cancer patient populations. Multilevel and multicomponent interventions that target care coordination, health system, and policy changes may enhance equitable access to and receipt of MDCc.